A Packet Delivery Cost Analysis of a Flow-Enabled Proxy NEMO Scheme in a Distributed Mobility Anchoring Environment - Shayla Islam; Mohammad Kamrul Hasan; Aisha Hassan Abdalla Hashim (Elektronika ir Elektrotechnika, 2020)
DMM (Distributed Mobility Management) is a present elective worldview for creating a mobility management scheme to discourse the centralized issues in present IP-based mobile environments. The main reason is to enable these schemes to adapt to the present increment in the number of mobile operators, as well as mobile information traffic size, just as the pattern in the mobile Internet towards Industry 4.0 in a flat architecture. Until this point, the advancement of schemes dependent on the DMM-based method is still at fundamental phases in the Internet Engineering Task Force (IETF), as well as there is no present standard set up. With the point of taking advantage of utilizing different interfaces all at once, this paper proposes an enhanced Flow-enabled Proxy NEMO scheme in a Distributed Mobility Anchoring (FPNEMO-DMA) environment. Besides, a mathematical approach is advanced to assess the performance of the proposed FPNEMO-DMA scheme and benchmark with the existing Nemo Basic Support Protocol (NBSP) and Proxy NEMO.